Characterization of Photoactivated Singlet Oxygen Damage in Single-Molecule Optical Trap Experiments - Landry, Markita P. (The Biophysical Society, 2009)
Optical traps or “tweezers” use high-power, near-infrared laser beams to manipulate and apply forces to biological systems, ranging from individual molecules to cells. Although previous studies have established that optical tweezers induce photodamage in live cells, the effects of trap irradiation have yet to be examined in vitro, at the single-molecule level. In this study, we investigate trap-induced damage in a simple system consisting of DNA molecules tethered between optically trapped polystyrene microspheres. We show that exposure to the trapping light affects the lifetime of the tethers, the efficiency with which they can be formed, and their structure. Moreover, we establish that these irreversible effects are caused by oxidative damage from singlet oxygen. This reactive state of molecular oxygen is generated locally by the optical traps in the presence of a sensitizer, which we identify as the trapped polystyrene microspheres. Trap-induced oxidative damage can be reduced greatly by working under anaerobic conditions, using additives that quench singlet oxygen, or trapping microspheres lacking the sensitizers necessary for singlet state photoexcitation. Our findings are relevant to a broad range of trap-based single-molecule experiments—the most common biological application of optical tweezers—and may guide the development of more robust experimental protocols.